2002
DOI: 10.1097/00006123-200207000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Pain with Spinal Cord Stimulation versus Alternative Therapies: Cost-effectiveness Analysis

Abstract: SCS is cost-effective in the long term, despite the initial high costs of the implantable devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
163
0
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(179 citation statements)
references
References 21 publications
2
163
0
12
Order By: Relevance
“…This price is the middle value al. 111 suggested that because of the lifespan of the pulse generator battery, these batteries needed replacement after 3.5 to 4.5 years. ABHI's model assumed that the pulse generator needs to be replaced once every 4 years.…”
Section: Neuropathic Pain Model Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This price is the middle value al. 111 suggested that because of the lifespan of the pulse generator battery, these batteries needed replacement after 3.5 to 4.5 years. ABHI's model assumed that the pulse generator needs to be replaced once every 4 years.…”
Section: Neuropathic Pain Model Resultsmentioning
confidence: 99%
“…This assumption was taken from a 5-year analysis of cost for CMM in Canada. 111 Patients that undergo SCS have costs additional to CMM including screening, device implant, device reimplant, etc. (Table 22).…”
Section: Costs Of Health States Monitoring and Treatments In The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Serious side effects were not reported. 4)One low quality study examined the cost-effectiveness of SCS (Kumar et al 2002). Patients who were referred for SCS but did not undergo electrode internalisation were used as controls.…”
Section: C11 (B4) Intramuscular Injections Of Botulinum Toxinmentioning
confidence: 99%
“…Mancia et al, 14 in a prospective, randomized, controlled, multicenter study, concluded that the patients with combined SCS and medical management were more costly to the healthcare system, but also had significant functional improvement. Kumar et al 15 16 concluded that ''in selected [complex regional pain syndrome] patients, SCS is a cost-effective option as an adjunct to conventional medical management.'' They also concluded that a rechargeable generator is the most cost-effective option, when the predicted generator longevity is >4 years, despite higher initial cost.…”
Section: Permanent Implantationmentioning
confidence: 99%